Language anxiety and its influence on the oral production of english of students at a public university in Lima – 2024 - Vilchez Guzmán, Sonia (2025)
The main objective of this research work was to establish the extent to which language anxiety influences the oral production of students from the Faculty of Education at UNMSM, Lima-2024. According to this, the methodology responded to a quantitative approach of an applied type with a descriptive level and an explanatory scope. The population was 70 university students from the English and Spanish degree. The instruments to measure each variable have been selected because they have a supporting technical sheet and a high level of reliability (0.728). For the language anxiety variable, the Foreign Language Classroom Anxiety (Horwitz et al., 1986) was considered, which contains 33 questions with five answer options. In the case of the second variable, the Reyes (2019) questionnaire was taken based on Morales' (2002) theory, it has 25 questions with five answer alternatives. The results showed that language anxiety had a low and significant influence (Nagelkerke 5.1% - Sig. = 0.202) on the oral production of the students in the study. Therefore, the general hypothesis was validated and the null hypothesis was rejected. Among other results, it was evident that a medium level of language anxiety predominated, while oral production was average. It was concluded that as long as there is an environment free of anxiety regarding exams, oral communication, or negative evaluations from teachers, students tend to acquire the target language better.